PENGARUH ASAM KARBONAT (H2CO3) TERHADAP KEKUATAN TUMBUKAN AGREGAT BATU KAPUR - K. Salain, I. M. Alit; W. Ardana, M. Dodiek; Tahriri, W. (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 2 Juli 2009, 2009)
Chalk or limestone is frequently used for backfill materials and for stabilizing foundation layers of highway because of it’s good support in bearing capacity. However it is known that carbonate acid (H2CO3), which is soluble in the ground water, can dissolve chalks or limestone chemically. The natural acid environment is able to decrease the strength (support capability) of backfill and foundation layer. This study is conducted to determine the effect of carbonate acid on aggregate collision strength value of limestone (aggregate impact value or AIV). The AIV value is one of the indicators used in measuring the strength of aggregate. The AIV indicates that the aggregate was not too strong to receive loads from the burden of vehicle’s wheel or other load while it is being compacted. The tests on limestone strength were conducted after soaking the limestone into carbonate acid solution in a series of acid concentration as follows: 5, 10, 15, 20, and 25 parts per million. The soaking process of each solution was carried out for 10, 15, 20, 25, and 30 days long. The basic design used was a Factorial Complete Random Design, which studied matters such as the variation of carbonate acid concentration and the variation of soaking time. Then the test results was analyzed using a Style Investigation Analysis, Least Significant Different test and Disperse Diagram The test results show that the variation of concentration from 5 to 25 parts per million does not significantly affect the strength of limestone aggregate impact, but the time soaking has a real effect. There is an interaction between the variations of carbonate acid concentration solution with the time of soaking.
Keywords: limestone, carbonate acid, aggregate impact value